2020
DOI: 10.1111/nph.16941
|View full text |Cite
|
Sign up to set email alerts
|

Where do leaf water leaks come from? Trade‐offs underlying the variability in minimum conductance across tropical savanna species with contrasting growth strategies

Abstract: Summary Plants continue to lose water from their leaves even after complete stomatal closure. Although this minimum conductance (gleaf‐res) has substantial impacts on strategies of water use and conservation, little is known about the potential drivers underlying the variability of this trait across species. We thus untangled the relative contribution of water leaks from the cuticle and stomata in order to investigate how the variability in leaf morphological and anatomical traits is related to the variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 65 publications
10
66
0
Order By: Relevance
“…However, no significant correlations were found between these three stomata parameters and the abaxial cuticular transpiration rates. Machado et al (2020) also observed that for evergreens there is no significant association between stomatal properties and leaf water leaks. Our data suggest that the variations in the abaxial cuticular transpiration rates from these eight tea germplasms likely resulted from other factors rather than stomatal characteristics ( Figure 4A ; Supplementary Figure S3 ).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…However, no significant correlations were found between these three stomata parameters and the abaxial cuticular transpiration rates. Machado et al (2020) also observed that for evergreens there is no significant association between stomatal properties and leaf water leaks. Our data suggest that the variations in the abaxial cuticular transpiration rates from these eight tea germplasms likely resulted from other factors rather than stomatal characteristics ( Figure 4A ; Supplementary Figure S3 ).…”
Section: Resultsmentioning
confidence: 86%
“…Ew Ad : the adaxial eipcuticular waxes; Iw Ad : the adaxial intracuticular waxes; Ew Ab : the abaxial eipcuticular waxes; Iw Ab : the abaxial intracuticular waxes. Machado et al (2020) studied 30 different native tree species, including drought deciduous and evergreen, and found that residual stomatal transpiration had a significant impact on the minimum conductance; the stomata distribution pattern in the epidermis was a key factor determining the variation in minimum conductance. To exclude the stomatal effects on the cuticular transpiration rate measurement, in this study the stomata density, guard cell length, and guard cell pair width were measured from SEM images (Supplementary Figure S3A).…”
Section: The Cuticular Transpiration Rates From Different Leaf Surfaces and Cuticular Compartmentsmentioning
confidence: 99%
“…Thereby, under mild drought stress conditions, plants still possessed favorable leaf and root hydraulic properties, which could be able to minimize the risk of excessive dehydration via a coordinated balance between leaf transpiration and water transport from root to leaf, consistent with the previous findings ( Brodribb and Holbrook, 2004 ; Creek et al, 2018 ). Moreover, stomatal properties (e.g., stomatal size and density) are responsible for leaf water leak even when stomata are fully closed, which have a great impact on plant water use strategies ( Machado et al, 2021 ). Dramatic higher stomatal density in flacca than in AC has been reported by Fang et al (2019) , which might explain the significant low K root accompanied by still relatively high E and K leaf in stressed flacca , representing an extensive hydraulic failure and dysfunction in the regulation of the plant water balance.…”
Section: Discussionmentioning
confidence: 99%
“…A significant barrier for the broad scale adoption of the M2021 theory in gas exchange systems is the necessity to measure g cw for which the best methods are still debated (Boyer, 2015a;Duursma et al, 2019;Márquez et al, 2022). Recent advances, emerging datasets and new methods for measuring g cw should accelerate the adoption of this new theory (Duursma et al, 2019;Machado et al, 2021;Márquez et al, 2022;Slot et al, 2021). Importantly, some aspects of gas exchange calculations are still uncertain and could change in the future.…”
Section: Discussionmentioning
confidence: 99%